PENGARUH METODE PENGOLAHAN TERHADAP KANDUNGAN TANIN DAN SIFAT FUNGSIONAL TEPUNG PROSO MILLET (Panicum miliaceum) - Putu Eka Ditya Mahendra; Ni Luh Ari Yusasrini; I Desak Putu Kartika Pratiwi (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
The aim of this research were to determine the effect of processing methods on tannin content, functional properties proso millet (Panicum miliaceum) flour and determine which method can produce the lowest tannin content and the best functional properties. The Completely Randomized Design (CRD) was used in this research with 4 type of processing method treatments, such as: direct method, germination method, fermentation method, and germination-fermentation method. The treatment was repeated four times to obtain 16 experimental units. Data from the research results were analyzed by variance and if the treatment had a significant effect, then followed by Duncan’s Multiple Range Test (DMRT). The results showed that the treatment of proso millet processing method had a highly significant effect (P <0.01) on yield, water content, ash content, tannin content, water absorption capacity, oil absorption capacity, swelling power, and solubility. The best treatment was produced by proso millet flour with germination-fermentation processing method was able to produce the lowest tannin content on 0.59% with a yield value 65.47%, water content 12.36%, ash content 1.45%, water absorption capacity 172.85%, oil absorption capacity of 107.73%, swelling power of 10.11 g / g, and water solubility index of 44.10%. Keywords: proso millet, processing method, tannin content, functional properties, flour.